Effects of irradiation processing of speciality protein products on nursery pig performance - Woodworth, J.C.; Webster, M.J.; James, B.W.; Real, D.E.; DeRouchey, Joel M.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three hundred weanling pigs (initially 13.4 lb and 20 ± 2 d of age) were used in a 14-d growth assay to determine the effects of irradiation processing of specialty protein products on nursery pig performance. Overall, irradiated of AP 920 and Peptide-Plus™ resulted in increased ADG compared to nonirradiated products. Irradiation of Peptide-Plus® improved feed efficiency compared to its nonirradiated form. Also, ADG was greater for pigs fed diets containing ProtiOne™ and DPS 30 and tended to increase with AP 920 compared to those fed the control diet. In addition, feed efficiency was improved for pigs fed diets containing ProtiOne™, DPS 30, Peptide-Plus™, and spray-dried egg compared to those fed the control diet. Therefore, adding specialty protein products to diets in most cases improved growth performance, and irradiation processing improved growth performance with certain specialty protein products.
Keywords: Swine; Nursery pigs; Irradiation; Speciality protein